Environmental Stringency, Corruption And Foreign Direct Investment (Fdi): Lessons From Global Evidence - Sarmidi, Tamat; Md Nor , Abu Hassan Shaari; Ridzuan, Sulhi (Asian Academy of Management (AAM), 2015)
Developing countries face a dilemma: to have either a stringent environmental policy that may lead to less foreign direct investment (FDI) or a less stringent environmental policy but more FDI through which economic growth may occur. Motivated by this paradox, it is necessary to examine the dynamic relationship between FDI, pollution control and corruption to suggest a mechanism that may be effective in combating the pollution haven effect. Using dynamic panel Generalised Method of Moments (GMM) estimation for 110 countries from 2005 to 2012, the findings suggest that the stringency in environmental control alone has had a negative effect on FDI, and at the same time, high levels of corruption have attracted FDI inflows. Interestingly, in contrast to previous findings, our results show that high stringency in environmental control coupled with low levels of corruption has attracted significantly more FDI inflows. In other words, ethical institutions could nullify the negative effect of stringency in pollution control to FDIs. This finding, besides its robustness to various environmental stringency measures, is a potential answer to the pollution haven effect for developing countries.